Green Sintesis Senyawa Kompleks Fe(III) dengan Ligan Basa Schiff 2-Metoksi-6-(((4- Metoksifenil)Imino)Metil)Fenol Menggunakan Metode Penggerusan pada Variasi Waktu 10; 20; dan 30 Menit - Mumtazah, Lulu Khoerul; Hanapi, Ahmad; Ningsih, Rachmawati (ALCHEMY:Journal of Chemistry, 2025)
Synthesis of the complex compound Fe(III) from the ligand 2-methoxy-6-(((4- methoxyphenyl)imino)methyl)phenol and FeCl3.6H2O using the grinding method has been carried out. The ligand 2-methoxy-6-(((4- methoxyphenyl)imino)methyl)phenol was synthesized from the reactants o-vanillin and p-anisidine. The synthesis results were tested for physical and chemical properties, characterization using FTIR and GC-MS. Meanwhile, the results of the synthesis of complex compounds were tested for physical properties and characterization using UV-Vis, FTIR, Jobs' method, AAS and the Kjeldahl method. The results of the Schiff base ligand characterization show the physical characteristics of powder form, brownish yellow color, and a melting point of 87 – 89 οC. Chemical properties tests showed that the product was soluble in 2M NaOH and slightly soluble in distilled water. The absorption of the imine group is formed at a wave number of 1620 cm-1. Ligand purity 100% with molecular ion (m/z) 257. Complex synthesis product at varying grinding times 10; 20; and 30 minutes each showed physical characteristics in the form of powder, blackish brown in color, and melting points of 178 – 181 οC respectively; 179 – 181 οC; and 178 – 182 οC. The complex compound shows a hypsochromic shift and the appearance of a d – d transition. The absorption of the imine functional group (C=N) is formed at wave numbers 1643 cm-1 and 1612 cm-1. The absorption of the Fe-O and Fe-N functional groups appears at wave numbers 532 cm-1 and 447 cm-1. The mole ratio of metal and ligand in complex compounds is 1:4. The iron (Fe) content is 5.1661% and the nitrogen (N) content is 5.4630%. These results show the prediction of the molecular formula of the complex compound, namely [Fe(III)(C15H15O3N)4].